Epidemiology of respiratory distress and the illness severity in late preterm or term infants： a prospective multi-center study - Ma, Xiao-lu; Xu, Xue-feng; Chen, Chao; Yan, Chao-ying; Liu, Ya-ming; Liu, Ling; Xiong, Hong; Sun, Hui-qing; Lai, Jian-pu; Yi, Bin; Shi, Jing-yun; Du, Li-zhong (Chinese medical journal, 2010)
Background The severity of respiratory distress was associated with neonatal prognosis. This study aimed to explore the clinical characteristics, therapeutic interventions and short-term outcomes of late preterm or term infants who required respiratory support, and compare the usage of different illness severity assessment tools.Methods Seven neonatal intensive care units in tertiary hospitals were recruited. From November 2008 to October 2009, neonates born at ≥34 weeks＇ gestational age, admitted at 〈72 hours of age, requiring continuous positive airway pressure （CPAP） or mechanical ventilation for respiratory support were enrolled. Clinical data including demographic variables, underlying disease, complications, therapeutic interventions and short-term outcomes were collected. All infants were divided into three groups by Acute care of at-risk newborns （ACoRN） Respiratory Score 〈5, 5-8, and 〉8.Results During the study period, 503 newborn late preterm or term infants required respiratory support. The mean gestational age was （36.8±2.2） weeks, mean birth weight was （2734.5±603.5） g. The majority of the neonates were male （69.4%）, late preterm （63.3%）, delivered by cesarean section （74.8%）, admitted in the first day of life （89.3%） and outborn （born at other hospitals, 76.9%）. Of the cesarean section, 51.1% were performed electively. Infants in the severe group were more mature, had the highest rate of elective cesarean section, Apgar score 〈7 at 5 minutes and resuscitated with intubation, the in-hospital mortality increased significantly. In total, 58.1% of the patients were supported with mechanical ventilation and 17.3% received high frequency oscillation. Adjunctive therapies were commonly needed.Higher rate of infants in severe group needed mechanical ventilation or high frequency oscillation, volume expansion,bicarbonate infusion or vasopressors therapy （P 〈0.05）. The incidence of complications was also increased significantly in severe group （P 〈0.05）. The in-hospital mortality in the severe group was significantly higher than other two groups （P〈0.05）. ACoRN Respiratory Score was correlated with Score for Neonatal Acute Physiology-Version Ⅱ （SNAP-Ⅱ） （P〈0.01）. High gestational age, high SNAP-Ⅱ score and oxygenation index （OI）, and Apgar score at 5 minutes 〈5 were independent risks for death.Conclusions Neonatal respiratory distress is still a common cause of hospitalization in China. Illness severity assessment is important for the management. ACoRN Respiratory Score which correlated with SNAP-Ⅱ score is easy to use and may be helpful in facilitating the caregivers in local hospital to identify the early signs and make the transfer decision promptly.